Belonging to (Not “in”) Land as Performed at Indigenous Cultural Events - Harvey, Graham (Material religion, 2022)
Drawing on research at two Indigenous festivals – Riddu Riđđu and the ORIGINS Festival of First Nations – this article considers ways in which Indigenous performers present their belonging to (not in) places. They are globally mobile but affirm reciprocal responsibilities with homelands. These two festivals bring together participants from across the world and provide an opportunity to consider further the dynamics of trans-Indigenous creativity. Enthused by performers at these festivals, and inspired by the critical reflections of Chadwick Allen (2012) and Robert Jahnke (2006), I reflect on some of the ways in which Indigenous performers – musicians, artists, artisans, authors, film-producers, poets and others – entertain, educate, and inspire their audiences. The following sections introduce the two festivals and they expand on Allen and Jahnke’s key terms. A selected performance at each of the festivals will then be used to exemplify and highlight the mobility of Indigenous people, traditions, and activities.